2016
DOI: 10.1038/srep32374
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-3713 regulates bladder cell invasion via MMP9

Abstract: Transitional cell carcinoma (TCC) is the most common type of bladder cancer but its carcinogenesis remains not completely elucidated. Dysregulation of microRNAs (miRNAs) is well known to be involved in the development of various cancers, including TCC, whereas a role of miR-3713 in the pathogenesis of TCC has not been appreciated. Here, we reported that significantly higher levels of matrix metallopeptidase 9 (MMP9), and significantly lower levels of miR-3713 were detected in TCC tissue, compared to the adjace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…MMP9 activity has been shown to be higher in invasive bladder cancer compared to normal control 58 . Knockdown of MMP9 by microRNAs in bladder cancer cells also resulted in decreased cell invasion 59 . However, the prognostic significance of MMP9 has not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…MMP9 activity has been shown to be higher in invasive bladder cancer compared to normal control 58 . Knockdown of MMP9 by microRNAs in bladder cancer cells also resulted in decreased cell invasion 59 . However, the prognostic significance of MMP9 has not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have demonstrated that miRNAs are involved in a number of cancer-associated biological processes, including cell proliferation, apoptosis, the cell cycle, invasion, migration and metastasis (13)(14)(15). Notably, miRNA dysregulation has been reported in the majority of types of human cancer, including bladder cancer (16), prostate cancer (17), glioma (18), gastric cancer (19) and osteosarcoma (20). Previous studies have revealed that abnormally expressed miRNAs may be correlated with tumorigenesis and tumor development (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…C-jun was an important oncogene that could provide signals for cell survival; it was highly overexpressed in various invasive cancers, and repression of c-jun was beneficial to inhibiting the development and progression of cancer [ 34 , 35 ]. MMP9 has been shown to be involved in the migration and invasion of various tumors, including breast cancer, transitional cell carcinoma, and non-small cell lung cancer [ 36 39 ]. A recent study revealed that epigenetic down-regulation of COL1A1 mRNA expression might have a role as a prognostic biomarker of hepatocellular carcinoma [ 40 ].…”
Section: Discussionmentioning
confidence: 99%